Marketing to the Digitally Empowered: How PalmPay Uses Blockchain to Reach the Unbanked in Iringa Municipal - Kibona, Lusekelo (Digital Technologies Research and Applications, 2025)
In the digital era, access to financial services has become a cornerstone for economic empowerment and inclusive growth. However, millions in developing regions such as Tanzania remain unbanked, lacking access to formal financial systems. With the growth of fintech innovations, platforms like PalmPay have emerged as crucial tools for bridging this financial gap. PalmPay, a mobile money and financial services platform, has gained widespread popularity across African markets for offering secure, convenient, and user-friendly digital transactions. When integrated with blockchain technology, PalmPay becomes even more effective by enhancing transparency, data security, and trust—elements that are often limited in developing economies. This study explored how PalmPay, as a blockchain-enabled digital financial platform, has been used to reach and serve the unbanked population in Iringa Municipal through strategic digital marketing approaches. Using a purposive sample of 58 respondents, data were collected through qualitative interviews and structured questionnaires focusing on awareness, trust, and adoption influenced by blockchain, as well as the effectiveness of digital marketing strategies. Findings revealed that while most respondents were aware of PalmPay, many had only a partial understanding of blockchain, mainly associating it with improved security and transparency. Trust and adoption were driven by PalmPay’s ability to provide real-time, traceable, and secure transactions, although a digital trust gap persisted among less digitally literate users. Mobile-based marketing campaigns, particularly SMS and in-app promotions, were most effective when localized and supported by personal engagement from community agents or peers. Word-of-mouth influence remained a strong driver of adoption, underscoring the need for community-based and culturally sensitive outreach strategies.